Peranan Promosi dan Distribusi Bisnis tterhadap Peningkatan Penjualan - Al Tasya Fitrah; Zuhrinal M. Nawawi (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
The current industrial business competition in producing and marketing products to consumers continues to get higher every year. The presence of various kinds of competitors in today's global industry is one factor that must be considered. Product quality, promotion and distribution are thought to have an important role in efforts to increase marketing performance in a business. Promotion is very closely related to a sale as a result, promotion is used and carried out on the marketing and sales of a product so that it gets an increase in sales of a business. Promotion can be done in various ways, one of which is through advertising. Promotion through advertising needs to be done through the media of newspapers, radio, magazines, social media, television, or in the form of posters placed on the side of the road or in strategic places. Therefore, as marketing, it is required to be able to carry out promotions appropriately so that it can be accepted by consumers and can increase product sales as expected by a business. Distribution is the act of getting products from producers to consumers at the right time. Therefore, distribution is one of the marketing policies that includes the identification of marketing channels (marketing). Distribution channels are used to facilitate sales transactions, introduce products from producers to consumers, and ensure Therefore, promotion and distribution will have an impact on the level of product sales in a business. This is because the more effective promotion and distribution are carried out, the more product sales increase.